Fundamental Understanding of Hydrogen Evolution Reaction on Zinc Anode Surface: A First-Principles Study - Liu, Xiaoyu; Guo, Yiming; Ning, Fanghua; Liu, Yuyu; Shi, Siqi; Li, Qian; Zhang, Jiujun; Lu, Shigang; Yi, Jin (Nano-Micro Letters, 2024)
Hydrogen evolution reaction (HER) has become a key factor affecting the cycling stability of aqueous Zn-ion batteries, while the corresponding fundamental issues involving HER are still unclear. Herein, the reaction mechanisms of HER on various crystalline surfaces have been investigated by first-principle calculations based on density functional theory. It is found that the Volmer step is the rate-limiting step of HER on the Zn (002) and (100) surfaces, while, the reaction rates of HER on the Zn (101), (102) and (103) surfaces are determined by the Tafel step. Moreover, the correlation between HER activity and the generalized coordination number<span id="MathJax-Element-1-Frame" class="MathJax_SVG" style="font-size: 100%; display: inline-block; position: relative;" tabindex="0" role="presentation" data-mathml="<mover>CN¯</mover>"> of Zn at the surfaces has been revealed. The relatively weaker HER activity on Zn (002) surface can be attributed to the higher <span id="MathJax-Element-2-Frame" class="MathJax_SVG" style="font-size: 100%; display: inline-block; position: relative;" tabindex="0" role="presentation" data-mathml="<mover>CN¯</mover>"> of surface Zn atom. The atomically uneven Zn (002) surface shows significantly higher HER activity than the flat Zn (002) surface as the <span id="MathJax-Element-3-Frame" class="MathJax_SVG" style="font-size: 100%; display: inline-block; position: relative;" tabindex="0" role="presentation" data-mathml="<mover>CN¯</mover>"> of the surface Zn atom is lowered. The <span id="MathJax-Element-4-Frame" class="MathJax_SVG" style="font-size: 100%; display: inline-block; position: relative;" tabindex="0" role="presentation" data-mathml="<mover>CN¯</mover>"> of surface Zn atom is proposed as a key descriptor of HER activity. Tuning the <span id="MathJax-Element-5-Frame" class="MathJax_SVG" style="font-size: 100%; display: inline-block; position: relative;" tabindex="0" role="presentation" data-mathml="<mover>CN¯</mover>"> of surface Zn atom would be a vital strategy to inhibit HER on the Zn anode surface based on the presented theoretical studies. Furthermore, this work provides a theoretical basis for the in-depth understanding of HER on the Zn surface. Highlights: 1 The reaction mechanisms of hydrogen evolution reaction (HER) on various crystal surfaces of zinc anode have been systematically investigated by first-principle calculations. 2 Both the thermodynamic and kinetic aspects of HER have been studied to reveal the relative HER activity of several crystal surface of zinc anode. 3 The generalized coordination number of surface Zn atoms are proposed as a key descriptor of HER activity of Zn anode.